Efficient market hypothesis in the presence of market imperfections: Evidence from selected stock markets in Africa - Ikechukwu Kelikume; Evans Olaniyi; Faith A. Iyohab (International Journal of Management, Economics and Social Sciences (IJMESS), 2020)
This paper investigated the weak axiom of the efficient market hypothesis (EMH) as it applies to fifteen (15) leading stock markets in Africa. There are currently over twenty-nine stock exchanges in Africa with a significant degree of disparities ranging from market size, trading volume, number of listed companies, access to funds, access to information to market standardization etc. The article deviated from the conventional linear approach of testing efficient market hypothesis and the method of using the runs test for serial dependency to test the weak-form efficient market hypothesis. The paper adopted the wavelet unit root analysis-tool, which decomposed the stochastic processes into its wavelet components, with varying frequency band. The study found that institutional constraints have implications for the efficient market hypothesis and investment in the African stock market. The conclusions drawn from the study is the relevance of using past historical stock prices to predict the current earnings at stock markets in Africa, a negation of the efficient market hypothesis.
Keywords: C01; C23; D84; GI4; 330; Efficient market; information asymmetry; stock prices; wavelet unit root; Africa